The Impact of Kitab Kuning Reading Habits on Arabic Vocabulary Mastery Among Islamic Boarding School Students - Mujibur Rohman; Munirul Abidin (Journal of Teaching and Learning, 2025)
Vocabulary is a crucial component in mastering the Arabic language, especially for students (santri) in Islamic boarding schools (pesantren) who regularly engage with classical Arabic texts such as kitab kuning. However, the lack of attention to systematic kitab kuning learning methods can hinder students’ vocabulary development. This study aims to determine the influence of kitab kuning reading habits on the Arabic vocabulary mastery of students at Illiyyin Dormitory, Darul Falah Amtsilati Islamic Boarding School. The research employs a quantitative associative approach using Pearson Product Moment correlation analysis. The sample consisted of 30 students selected purposively based on their active participation in kitab kuning learning. Data were collected through a reading habit questionnaire and an Arabic vocabulary test. The analysis revealed a very strong and significant relationship between kitab kuning reading habits including reading duration, discipline, comprehension and vocabulary mastery (r = 0.986; p = 0.000). These findings highlight the importance of structured kitab kuning reading practices in enhancing Arabic vocabulary acquisition and call for the implementation of contextual and tiered pedagogical strategies in pesantren settings to support equitable and effective learning outcomes.